2021
DOI: 10.1016/j.jebo.2021.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Self-Selection into corruption: Evidence from the lab

Abstract: We study whether opportunities to extract rents in a job affect the type of individuals who are attracted to it in terms of their underlying integrity. We do so in a laboratory experiment in which participants choose between two contracts that involve different tasks. We experimentally introduce the possibility of graft in one of them and study the sorting of subjects across contracts based on an incentivized measure of honesty. We find that the corruptible contract changes the composition of subjects because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…These subjects appear to use a simple heuristic of maximizing their legal monetary payoffs in occupation choice. 9 It is quite conceivable that many subjects, despite being altruistic and moral in other domains, may use the heuristic of legal monetary maximization in occupation choice and then use their payoffs to exhibit altruism elsewhere, e.g., contribute to charity. They might also be 8 A potential explanation, which is not a part of our model, and neither tested in our experimental results, is guilt-aversion.…”
Section: Our Results Are As Followsmentioning
confidence: 99%
See 2 more Smart Citations
“…These subjects appear to use a simple heuristic of maximizing their legal monetary payoffs in occupation choice. 9 It is quite conceivable that many subjects, despite being altruistic and moral in other domains, may use the heuristic of legal monetary maximization in occupation choice and then use their payoffs to exhibit altruism elsewhere, e.g., contribute to charity. They might also be 8 A potential explanation, which is not a part of our model, and neither tested in our experimental results, is guilt-aversion.…”
Section: Our Results Are As Followsmentioning
confidence: 99%
“…Formal modeling will need to consider explicitly beliefs-based models using the machinery of psychological game theory (see Dhami et al, 2019; and also consider the endogeneity of the preference parameters themselves. 9 The evidence increasingly shows that in making choices, many people use simple context-dependent heuristics (Dhami and Sunstein, 2022).…”
Section: Our Results Are As Followsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet another study found that those more willing to cheat were also more likely to opt for information that facilitated justification of dishonest behavior (Akin, 2019). Most recently, Brassiolo, Estrada, Fajardo & Vargas (2020) demonstrated that in comparison with conditions using artificial tokens, conditions enabling embezzlement of real money drove away honest individuals while attracting those more willing to cheat. Given the relative lack of attention to selection effects in the research on dishonesty, the primary aim of this paper is to analyze these effects and their relationship to cheating.…”
Section: Introductionmentioning
confidence: 99%